1994
DOI: 10.1113/jphysiol.1994.sp020169
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of inhibitory neurones in the guinea‐pig hippocampus in vitro.

Abstract: 1. Intracellular recordings were obtained from pyramidal, granule and hilar cells in transverse slices of guinea-pig hippocampus to examine synaptic interactions between GABAergic neurones. 2. In the presence of the convulsant compound 4-aminopyridine (4-AP), after fast excitatory amino acid (EAA) neurotransmission was blocked pharmacologically, large amplitude inhibitory postsynaptic potentials (IPSPs) occurred rhythmically (every 4-8 s) and synchronously in all principal cell populations (triphasic synchroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 43 publications
11
88
0
Order By: Relevance
“…As Glu concentration can be 1,000-fold higher in the blood than in the extracellular space of the brain, a barrier to this amino acid is essential to allow a normal neuronal and synaptic activity (1). In contrast, picrotoxin, a ␥-aminobutyric acid antagonist, can easily cross the BBB and can induce epilepsy in animals (67,68). Our results indicate that Glu was prevented from reaching the nervous tissue in the coculture assemblies, whereas the picrotoxin epileptogenic effect was observed, as expected, in both control and cocultures.…”
Section: Discussionmentioning
confidence: 99%
“…As Glu concentration can be 1,000-fold higher in the blood than in the extracellular space of the brain, a barrier to this amino acid is essential to allow a normal neuronal and synaptic activity (1). In contrast, picrotoxin, a ␥-aminobutyric acid antagonist, can easily cross the BBB and can induce epilepsy in animals (67,68). Our results indicate that Glu was prevented from reaching the nervous tissue in the coculture assemblies, whereas the picrotoxin epileptogenic effect was observed, as expected, in both control and cocultures.…”
Section: Discussionmentioning
confidence: 99%
“…4AP application results in downregulation of the KCC2 co-transporter in hippocampal slices, resulting in intracellular CI-accumulation and hence depolarizing postsynaptic responses to GABA (Rivera et aL, 2004). It is thus possible that these potentials were not completely abolished despite the presence of DAGO due to strong somatic excitation mediated by interneuron recurrent collateral release of depolarizing GABA, to lead to large synchronized interneuronal network discharges (Michelson and Wong, 1994 (Delfs et aL, 1994;Burkey et aL, 1996;Jasmin et aL, 2003). The increased abundance of IJ-opioid receptors within the IC therefore may account for differences in response to DAGO between the PC and the IC, however more experimentation would be necessary to determine precisely how these phenomena relate.…”
Section: ~-Opioid Receptor Modulation Of Synchronous Glutamate-indepementioning
confidence: 99%
“…In the hippocampus and neocortex, these potentials are the result of synchronized discharges of interneuronal networks Michelson and Wong, 1994;Avoli et aL, 1996;Lamsa and Kaila, 1997), and appear to play a role in the initiation of in vitro ictal discharges in the EC . We found that these potentials occur within the PC and the IC synchronously without a preferential site of initiation.…”
Section: ~-Opioid Receptor Modulation Of Synchronous Glutamate-indepementioning
confidence: 99%
See 1 more Smart Citation
“…There is now little doubt that gap junctions play a substantial role in the generation of neural rhythms [28,5], both functional [25,1,28,5] and pathological [17,51]. One natural question therefore is how does the presence of gap junction coupling affect synchronous neuronal firing [40,24,4]. Independent experimental studies have proposed that gaps synchronize neuronal firing even in the absence of chemical synapses [16,37].…”
Section: Introductionmentioning
confidence: 99%